Customer Experience Dimension on Word of Mouth (EWOM) and The Intention to Revisit The Lounge of an Airline at Airport - Sela, Shiyrah Theosebes; Kuswindi, Bintarina; Nurlitha Sir, Putri (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Sumatera Utara, 2024)
Purpose – This research aims to explore the customer experience through its factors which are cognitive, emotional, and sensory evaluation on Word of Mouth (EWOM) and the intention to revisit. This research will investigate the perceived comfort together with customer satisfaction.Methodology – This research used a quantitative method with a cross sectional study approach. Primary data was collected online using Google Form as the questionnaire. The respondents were the visitors of Batik Air Lounge at Soekarno-Hatta airport. A probability sampling technique was used with a simple random sampling technique. Confirmatory Factor Analysis was used to test the research instrument. Structural Equation Model was used to analyze data.Findings – This research found that cognitive evaluation has no effect on perceived comfort, while the emotional and sensory evaluation do. The cognitive, emotional, and sensory evaluation have effect on the customer satisfaction. The perceived comfort has the effect on customer satisfaction, and together influence the Word of Mouth (WOM) that may lead customer to revisit.Originality/Novelty – The novelty of this research are the perception and the satisfaction of customer are found to be able to influence the WOM and intention to revisit.Implications – This research suggests building the perception and satisfaction of customer to influence the WOM that create an intention of customer to revisit.